PENGARUH TRUST TERHADAP TAX AVOIDANCE - Sitardja, Meco; Waluyo, Waluyo (Lembaga Penerbitan Unversitas Esa Unggul, 2020)
This study analyzes the effect of Trust in government on Tax Avoidance. This research is based on agency theory where the Tax Institution as the agent and Taxpayer as the principal. This study uses 80 samples of non-financial sector companies listed on the Indonesia Stock Exchange in 2019 with a purposive sampling method. The analysis uses multiple regression to see the effect of General Trust, Ability, Benevolence and Integrity on Tax Avoidance. Empirical results show that General Trust, Ability and Benevolence have a positive effect on Tax Avoidance. On the other hand, Integrity does not have an influence because it is considered as an abstract factor for taxpayers to determine their attitude to comply with taxes or avoid taxes. The research implication for TaxÂ InstitutionÂ is the need to increase disclosure of information related to tax benefits for the public so that the Director General of Taxes can be considered as a Wealth Agent for all taxpayers. For further research, research can be developed Social Norm factors on tax avoidance because it becomes a strong impetus for individuals and companies to behave in relation to tax avoidance.